Role of Sigma Receptors in Alcohol Addiction - Quadir, Sema G.; Cottone, Pietro; Sabino, Valentina (Frontiers in Pharmacology, 2019)
Pharmacological treatments for alcohol use disorder (AUD) are few in number and often ineffective, despite the significant research carried out so far to better comprehend the neurochemical underpinnings of the disease. Hence, research has been directed towards the discovery of novel therapeutic targets for the treatment of AUD. In the last decade, the sigma receptor system has been proposed as a potential mediator of alcohol reward and reinforcement. Preclinical studies have shown that the motivational effects of alcohol and excessive ethanol consumption involve the recruitment of the sigma receptor system. Furthermore, sigma receptor antagonism has been shown to be sufficient to inhibit many behaviors related to AUDs. This paper will review the most current evidence in support of this receptor system as a potential target for the development of pharmacological agents for the treatment of alcohol addiction.